Zero-Gap Alkaline Water Electrolysis Using Ion-Solvating Polymer Electrolyte Membranes at Reduced KOH Concentrations. Issue 11 (21st July 2016) - Kraglund, Mikkel Rykær; Aili, David; Jankova, Katja; Christensen, Erik; Li, Qingfeng; Jensen, Jens Oluf
Abstract : Membranes based on poly(2, 2 ′ -( m -phenylene)-5, 5-bibenzimidazole) ( m -PBI) can dissolve large amounts of aqueous KOH to give electrolyte systems with ion conductivity in a practically useful range. The conductivity of the membrane strongly depends on the concentration of the aqueous KOH phase, reaching about 10 −1 S cm −1 or higher in 15–25 wt% KOH. Herein, m -PBI membranes are systematically characterized with respect to performance and short-term stability as electrolyte in a zero-gap alkaline water electrolyzer at different KOH concentrations. Using plain uncatalyzed nickel foam electrodes, the cell based on m -PBI outperforms the cell based on the commercially available state-of-the-art diaphragm and reaches a current density of 1500 mA cm −2 at 2.4 V in 20 wt% KOH at 80°C. The cell performance remained stable during two days of operation, though post analysis of the membrane using size exclusion chromatography and spectroscopy reveal evidence of oxidative degradation of the base polymer at KOH concentrations of 15 wt% and higher.